Potential of madre de agua (trichanthera gigantea) leaves as an alternative protein source in fish diet on the growth performance of red tilapia (oreachromis spp.) juveniles - Caroline Seraphina David (2024)
As the worldwide is depending on the same protein for fish feed and human food, an alternative protein from plant-based is relevant. Trichanthera gigantea presents promising prospects as an alternative protein for fish. The research methodology involves formulating experimental diets with varying inclusion levels of Trichanthera gigantea leaves and assessing their effects on the growth performance of red tilapia (Oreochromis spp.). Trichanthera gigantea is known with its high in protein content. Trichanthera gigantea contain 18.21% crude protein, 12.5% crude fiber, 2.66% crude fat, 88.44% dry matter, 21.80% ash and 11.56% moisture content. The trials are through controlled feeding trial for 60 days with 4 different treatments: 0% MDA, 10% MDA, 20% MDA and 30% MDA with triplicates respectively. 120 juveniles were randomly assigned into 4 dietary treatments which consists of 10 juveniles per tank. The fish stage that were used is the juveniles with length for about 2 inches and weight 0.5-0.7 grams. Growth performance is determined from the total body length (TL, cm), body weight (BW, g), feed intake (FI), feed frequency, feed conversion ratio (FCR), feed efficiency ratio (FER), specific growth rate (SGR) and mortality rate. The results show that fish fed with 10% inclusion level gave the best growth performance. On the other hand, fish fed with 20% and 30% of leaf meal resulted in the slowest growth and having the lowest survival rate.
Projectpaper B.S.(Hons) Aqua - Universiti Putra Malaysia, 2024.
English.
Keywords: Fishes -- Breeding; Fish hatcheries; Online project paper